An Expert System for Diagnostic Construction Problems in Pavement (Flexible, Rigid, Composite , Block or Brick Pavement) in Addition to Subgrade and Subbase Condition Defects (ES-DATPs) - Muhammad Khidre Musa, Shahban Ismael Albrka (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Construction of roadway pavement entail significant issues that are impacted by various factors and are nearly impossible to overcome without expert assistance. Treatment and maintenance such challenges in pavement and providing the best economical solutions requires substantial technical competence, which owing to scarce resources and far-flung locations might not be accessible at every construction site. Establishing an expert system in this scope is a highly impressive method for assisting debutant engineers in overcoming and learning about these challenges. Interviews and questionnaires are used to obtain more expert information. This information is recorded, analyzed, represented, and converted to computer application through the Visual Studio language of programming, and the system is valled as ES- DATPS. The main aim of creating this expert system (ES- DATPS) is to helps highway engineers and civil engineers to acquaint causes, prevention, degree of severity, testing, measurement, maintenance and repair of all problems for (rigid pavement, flexible pavement, composite pavement, block or brick pavement) in addition to subbase and subgrade defects with accuracy and detail. According to the degree of severity, the best practice and economic method for maintenance each type of pavement can be selected by engineers. This expert system helps highway engineers to manage challenges and recognize type of defects by figures and video